Effectiveness of Instruction Program on Caregiver Knowledge concerning Emergency Care for Geriatrics at Al-Russafa Geriatric Home in Baghdad City - Ali R. Ibrahim; Huda B. Hassan (Journal of Madenat Alelem University College, 2019)
Objective: 1- To evaluate the effectiveness of an instructional program on caregiver in geriatrics home2- To find-out the relationship between the effectiveness of the instruction program and level of education, training course, and year of experiences of caregiverMethodology: A quasi-experimental design study is conducted at geriatric home in AL – Russafa sector in Baghdad City which as (Al Cyelikh, and AL- Rashad) . The study was started at 13rd of December 2018 to 7 February 2019. randamly sample of (20) caregiver works in geriatric home were studied . Data were collected throughout the utilization of the adopted questionnaire and interview technique. The questionnaire was consists of (48) items related to emergency care for emergency situation for geriatrics persons, the reliability of instrument was 0.84 by using cronbachs alpha, the data analysis done by using the statistical methods which include (descriptive, and inferential statistics)  Results: The socio-demographic characteristics of caregiver who participate in present study were most nurses of them, 80%, 60% in Al Cyelikh, and AL- Rashad geriatric  home, respectively most of them  have experiences in age 39-48 years old, high percent of them graduated from college,  and live in urban area, 70%, and 80% of caregiver  in Al Cyelakh, AL- Rashad geriatric  home respectively have had emergency cases in their  work shift, 85%, 90% of cases was saved in both geriatric  home    respectively, and there were effectiveness of instructional on caregiver knowledge toward the management of emergency cases throughout  the total mean at pre and post test which of  (1.2 and 1.2) (moderate level), to (1.7 and 1.7)   high level of knowledge for Al Cyelikh, and AL- Rashad geriatric  home respectively.Conclusion: the study concluded that there were positive effect of instruction program on caregiver knowledge toward emergency care of geriatric personsRecommendations: The study recommends to intensification training courses inside and outside the country and encourages employees to use safety measures to avoid injuries to the elderly persons.